2011
DOI: 10.1097/maj.0b013e3181f80248
|View full text |Cite
|
Sign up to set email alerts
|

Transbrachial Intra-Aortic Balloon Pumping for High-Risk Percutaneous Coronary Intervention

Abstract: The beneficial effect of placement of intra-aortic balloon (IAB) pump before revascularization in patients with high-risk coronary anatomy and impaired left ventricular systolic function is documented. However, the conventional insertion of IAB pump via the common femoral artery may be contraindicated or may be even impossible in patients with severe vascular disease. Recently, the percutaneous insertion of IAB via the brachial artery has been shown to be effective and safe in small series of patients with vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The transbrachial route has been shown to be safe and efficacious for IABP insertion in patients undergoing percutaneous coronary intervention7 8 and in patients undergoing coronary bypass surgery 9 10. Percutaneous placement of IABP in axillary/subclavian position has been described as a bridge to heart transplantation 4.…”
Section: Discussionmentioning
confidence: 99%
“…The transbrachial route has been shown to be safe and efficacious for IABP insertion in patients undergoing percutaneous coronary intervention7 8 and in patients undergoing coronary bypass surgery 9 10. Percutaneous placement of IABP in axillary/subclavian position has been described as a bridge to heart transplantation 4.…”
Section: Discussionmentioning
confidence: 99%
“…Another study (5) demonstrated safe insertion of a TBIAB in a patient with bilateral aortofemoral grafts undergoing successful stenting of a trifurcating left main stenosis.…”
Section: Discussionmentioning
confidence: 99%